Generations in Touch : Linking the Old and Young in a Tokyo Neighborhood - Thang, Leng Leng (Book collections on Project MUSE., 2018)
A dilemma long faced by western societies--how to bring the generations together--is also of growing concern in the east. In Japan, where, until recently, the extended family often lived under the same roof, social programs designed to facilitate ...